The leavening of bread - Vandivert, Harriet Agnes (My University, 1897)
Introduction: From the time the flour, yeast and wetting are mixed into a dough, until the fresh white slices of bread are placed upon the table to eat, a certain pleasure is felt by the cook in the accomplishment of so dainty a task, for a perfect loaf of bread represents to her, what deft hands and a clear brain may do, and proclaims her the possessor of a talent worth acquiring. She is now a lady—a loaf giver. The cook of a household is wise if she is mistress of this art of bread-making, for the perfectness of this “Staff of Life” means much towards the welfare of the persons who may eat of the food. Let her remember that she is, through her cookery, responsible for the habits and desires of the persons for whom she prepares the meals, and that to bear this responsibility rightly she must be an adept in all branches of cookery as well as in that one of bread-making.
Citation: Vandivert, Harriet Agnes. The leavening of bread. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Bread; Leavening; Domestic science; Theses; Manuscripts (documents)